Nonalcoholic fatty liver disease: biomarkers as diagnostic tools for liver damage assessment in adult patients from Argentina - Bertot, Gustavo (2020)
Fil: Bertot, Gustavo. Instituto Universitario de Ciencias de la Salud. Fundación Barceló; Argentina..